The Trans-Pacific Partnership: Is It Everything We Feared for Health? - Ronald Labonté; Ashley Schram; Arne Ruckert (Kerman University of Medical Sciences, 2016)
Background: Negotiations surrounding the Trans-Pacific Partnership (TPP) trade and investment agreement have recently concluded. Although trade and investment agreements, part of a broader shift to global economic integration, have been argued to be vital to improved economic growth, health, and general welfare, these agreements have increasingly come under scrutiny for their direct and indirect health impacts. Methods: We conducted a prospective health impact analysis to identify and assess a selected array of potential health risks of the TPP. We adapted the standard protocol for Health impact assessments (HIAs) (screening, scoping, and appraisal) to our aim of assessing potential health risks of trade and investment policy, and selected a health impact review methodology. This methodology is used to create a summary estimation of the most significant impacts on health of a broad policy or cluster of policies, such as a comprehensive trade and investment agreement. Results: Our analysis shows that there are a number of potentially serious health risks associated with the TPP, and details a range of policy implications for the health sector. Of particular focus are the potential implications of changes to intellectual property rights (IPRs), sanitary and phytosanitary measures (SPS), technical barriers to trade (TBT), investor-state dispute settlement (ISDS), and regulatory coherence provisions on a range of issues, including access to medicines and health services, tobacco and alcohol control, diet-related health, and domestic health policymaking. Conclusion: We provide a list of policy recommendations to mitigate potential health risks associated with the TPP, and suggest that broad public consultations, including on the health risks of trade and investment agreements, should be part of all trade negotiations.